Mechanism of hypoxia-induced damage to the mechanical property in human erythrocytes—band 3 phosphorylation and sulfhydryl oxidation of membrane proteins - Yang, Qinqin; Chen, Dong; Li, Chungong; Liu, Runjing; Wang, Xiang (Frontiers in Physiology, 2024)
The integrity of the erythrocyte membrane cytoskeletal network controls the morphology, specific surface area, material exchange, and state of erythrocytes in the blood circulation. The antioxidant properties of resveratrol have been reported, but studies on the effect of resveratrol on the hypoxia-induced mechanical properties of erythrocytes are rare.In this study, the effects of different concentrations of resveratrol on the protection of red blood cell morphology and changes in intracellular redox levels were examined to select an appropriate concentration for further study. The Young's modulus and surface roughness of the red blood cells and blood viscosity were measured via atomic force microscopy and a blood rheometer, respectively. Flow cytometry, free hemoglobin levels, and membrane lipid peroxidation levels were used to characterize cell membrane damage in the presence and absence of resveratrol after hypoxia. The effects of oxidative stress on the erythrocyte membrane proteins band 3 and spectrin were further investigated by immunofluorescent labeling and Western blotting.Resveratrol changed the surface roughness and Young's modulus of the erythrocyte membrane, reduced the rate of eryptosis in erythrocytes after hypoxia, and stabilized the intracellular redox level. Further data showed that resveratrol protected the erythrocyte membrane proteins band 3 and spectrin. Moreover, resistance to band 3 protein tyrosine phosphorylation and sulfhydryl oxidation can protect the stability of the erythrocyte membrane skeleton network, thereby protecting erythrocyte deformability under hypoxia. The results of the present study may provide new insights into the roles of resveratrol in the prevention of hypoxia and as an antioxidant.